PENGARUH LABEL HALAL, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK LIPSTIK WARDAH (Studi Kasus Pada Konsumen Lipstik Wardah Di Kota Pontianak) - admin, SYF. RAUDATUL AULIA B1021131007 (Jurnal Manajemen Update, 2017)
This research is aimed to know the effect of halal label, quality product, and brand image to consumer purchasing decision of wardah lipstick. The type of research a method of association which aims to using determine the relationship of causality between variables through hypothesis testing through a statistical calculation to obtain the results of evidence that shows the hypothesis rejected or accepted. Population in these research as many as there are 100 consumer of wardah lipstick in pontianak. Sampling method in this research using purposive sampling technique, and using questionnaire method for data collection. The data obtained were analyzed using instrument test consisting of validity test, and reliability and classical assumption test. Whereas hypothesis test using t test and multiple linear analysis. The results showed that quality product significantly influence purchasing decisions while halal label and brand image has no significant effect on purchasing decision. The ability of halal label, product quality and brand image as independent variable in explaining the effect on purchasing decision as dependent variable is 47,2% which is that in medium category while the rest equal to 52,8% influenced by other variable not examined in this research. Keywords: Halal Label, Quality Product, Brand Image and Purchase Decision